Effects of smoking on the association of human leukocyte antigen with ulcerative colitis. Issue 10 (19th June 2019) - Lee, Ho‐Su; Kim, Kihyun; Jung, Seulgi; Hong, Myunghee; Kim, Byoung Mok; Yoo, Dae‐sung; Moon, Jung Won; Baek, Jiwon; Hwang, Sung Wook; Park, Sang Hyoung; Yang, Suk‐Kyun; Han, Buhm; et al.
Abstract: Background and Aim: Tobacco smoking is a risk factor for gastrointestinal disorders, causing mucosal damage and impairing immune responses. However, smoking has been found to be protective against ulcerative colitis (UC). Human leukocyte antigen (HLA) is a major susceptibility locus for UC, and HLA‐DRB1*15:02 has the strongest effect in Asians. This study investigated the effects of smoking on the association between HLA and UC. Methods: The study enrolled 882 patients with UC, including 526 never, 151 current, and 205 former smokers, and 3091 healthy controls, including 2124 never, 502 current, and 465 former smokers. Smoking‐stratified analyses of HLA data were performed using a case–control approach. Results: In a case–control approach, HLA‐DRB1*15:02 was associated with UC in never smokers (ORnever smokers  = 3.20, P never smokers  = 7.88 × 10 −23 ) but not in current or former smokers ( P current smokers  = 0.72 and P former smokers  = 0.33, respectively). In current smokers, HLA‐DQB1*06 was associated with UC (ORcurrent smokers  = 2.59, P current smokers  = 6.39 × 10 −12 ). No variants reached genome‐wide significance in former smokers. Conclusions: An association between UC and HLA‐DRB1*15:02 was limited to never smokers. Our findings highlight that tobacco smoking modifies the effects of HLA on the risk of UC.